2015
DOI: 10.1186/s12883-015-0268-6
|View full text |Cite
|
Sign up to set email alerts
|

Thinner changes of the retinal nerve fiber layer in patients with mild cognitive impairment and Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is the most common form of dementia and patients often have visual disorders. Mild cognitive impairment (MCI) is characterized by a memory deficit when compared with those of a similar age and education level which could indicate an earlier onset of AD. The aim of this study is to measure the changes of the retinal nerve fiber layer (RNFL) thickness of AD and MCI patients in comparison with the normal age controls.MethodsThe RNFL thickness was assessed using optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 35 publications
(33 reference statements)
10
112
1
5
Order By: Relevance
“…No statistically significant differences in GC-IPL thickness between AD and MCI most affected. While some studies report preferential superior quadrant RNFL thinning in AD, which would explain the predominantly inferior visual field defects previously described in AD [40,45,47,54,[70][71][72], other authors have reported different findings; these results are presented in Table 1. A meta-analysis of TD-OCT studies in AD demonstrated that peripapillary RNFL thinning occurred in all retinal quadrants [73].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 91%
See 1 more Smart Citation
“…No statistically significant differences in GC-IPL thickness between AD and MCI most affected. While some studies report preferential superior quadrant RNFL thinning in AD, which would explain the predominantly inferior visual field defects previously described in AD [40,45,47,54,[70][71][72], other authors have reported different findings; these results are presented in Table 1. A meta-analysis of TD-OCT studies in AD demonstrated that peripapillary RNFL thinning occurred in all retinal quadrants [73].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 91%
“…Whether or not a correlation exists between retinal changes and severity of dementia also remains a controversial issue. While most OCT studies did not show correlation between Minimal Mental State Examination (MMSE) and peripapillary RNFL thinning (Table 2), one TD-OCT study reported correlation between MMSE scores and macular volume [44], and more recent studies using SD-OCT have indeed reported a significant correlation between MMSE scores and RNFL thickness [50,66,72,76,77]. Studies comparing changes in RNFLT in MCI and AD (Table 2) have also yielded conflicting results, although the majority reported no statistically significant differences between MCI and AD patient groups [46,47,54,77].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…Although reports of NFL thinning vary, there appears to be an overwhelming majority of evidence supporting a significant thinning of the superior quadrant of the NFL in the AD retina (Fig. 2) [19, 62, 79, 87, 104, 110, 113, 118, 121, 137, 142, 145147, 160, 177]. …”
Section: Non-specific Ocular Abnormalities In Ad Patientsmentioning
confidence: 99%
“…They also found significant reduction of the macular volume in MCI patients. Other authors showed that the RNFL thickness measurements were reduced in the superior quadrant and the total mean values are gradually and significantly decreased in patients ranging from MCI to severe AD, when compared to the controls [41]. In a systematic review and meta-analysis, Thomson et al [39] identified five studies including 214 MCI eyes and 421 control eyes), demonstrating a significant reduction in the overall mean RNFL thickness and in all four quadrants (superior, nasal, temporal and inferior) in patients with MCI.…”
Section: Optical Coherence Tomography Parameters In Mild Cognitive Immentioning
confidence: 99%